A prospective study of the bedside index for severity in acute pancreatitis (BISAP) score in predicting severity and prognosis of acute pancreatitis - V., Haridas T.; K., Asif Iqbal I. (International Surgery Journal, 2019)
Background: The aim of this study was to evaluate the ability of Bedside Index for Severity in Acute Pancreatitis (BISAP) score in predicting the severity and prognosis in patients admitted with acute pancreatitis. Methods: A prospective study was performed on 52 patients who presented with acute pancreatitis during the study period between January 2016 to November 2016. BISAP score was calculated for the patients. The disease was classified as mild or severe on the basis of presence of organ system failure and local/systemic complications. The accuracy of BISAP score in predicting the severity and prognosis of acute pancreatitis was evaluated. Results: Of the 52 patients studied, 11 patients had BISAP ≥2 and 41 patients had BISAP score <2. 9 of the 11 patients who had BISAP score ≥2 developed severe pancreatitis, local or systemic complications and had poor prognosis. 37 of the 41 patients who had BISAP score < 2 developed mild pancreatitis. Conclusions: BISAP score is accurate in predicting severity and prognosis of acute pancreatitis. Patients with BISAP score ≥2 developed severe pancreatitis and carried poor prognosis than patients with BISAP score <2.